2018
DOI: 10.1097/pcc.0000000000001551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a PICU Status Asthmaticus De-Escalation Pathway on Length of Stay and Albuterol Use*

Abstract: Implementation of a PICU asthma de-escalation pathway demonstrated statistical decrease in the reported measures for children with status asthmaticus. Although the clinical significance of these changes may be debatable, the results demonstrate that efforts to standardize asthma care in the PICU setting is an area in need of further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Although respiratory scores are applied in many clinical contexts, their performance cannot be determined solely on the perception of objectivity or functionality (face value), but rather by their capacity to be discriminative, predictive and evaluative in standardizing care, enhancing decision making, and offering risk stratification 7 . For instance, clinical scores in pediatric asthma are associated with reductions in LOS and continuous albuterol duration 17–19 . To standardize assessment of clinical scores, the COSMIN taxonomy have been proposed and consist of four primary test domains: validity, reliability, responsiveness, and interpretability 13 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although respiratory scores are applied in many clinical contexts, their performance cannot be determined solely on the perception of objectivity or functionality (face value), but rather by their capacity to be discriminative, predictive and evaluative in standardizing care, enhancing decision making, and offering risk stratification 7 . For instance, clinical scores in pediatric asthma are associated with reductions in LOS and continuous albuterol duration 17–19 . To standardize assessment of clinical scores, the COSMIN taxonomy have been proposed and consist of four primary test domains: validity, reliability, responsiveness, and interpretability 13 …”
Section: Discussionmentioning
confidence: 99%
“…7 For instance, clinical scores in pediatric asthma are associated with reductions in LOS and continuous albuterol duration. [17][18][19] To standardize assessment of clinical scores, the COSMIN taxonomy have been proposed and consist of four primary test domains: validity, reliability, responsiveness, and interpretability. 13 Validity includes face validity (qualitative judgment that a score is "good" or not by "experts"), content validity (appropriate representation of concept within the items of the score), construct validity (extent to which a score relates to other outcomes), and criterion-concurrent validity (degree to which a score relates to a gold-standard).…”
Section: Construct Validitymentioning
confidence: 99%
“… 8 12 Recently, quality improvement efforts in PICUs have shown promise to decrease the LOS and length of time spent receiving continuous nebulized bronchodilator treatments. 13 15 These studies have used various objective asthma scores combined with standardized algorithms to de-escalate care. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“… 13 15 These studies have used various objective asthma scores combined with standardized algorithms to de-escalate care. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Patients admitted to the PICU were included in these studies, but outcomes for subjects in the PICU were not specifically evaluated. [9][10][11][12][13] Brennan et al 14 recently found that a de-escalation pathway was associated with modest decreases in PICU LOS, hospital LOS, and duration of continuous albuterol therapy.…”
Section: Introductionmentioning
confidence: 99%